PEMBELAJARAN ONLINE SEBAGAI OBAT PADA PANDEMI COVID-19 - Ediwarman Ediwarman (Universitas Sultan Ageng Tirtayasa, 2021)
Schools in Indonesia are currently based on traditional learning methods. They follow the traditional setting of face-to-face schools in classrooms. Even though many schools have started mixed learning, many of them are stuck with old procedures. The Covid-19 Pandemic caused by the Corona Virus rocked the entire world. The World Health Organization declared it a pandemic. This situation challenges education systems around the world and forces educators to switch to online teaching mode overnight. Many schools that were previously reluctant to change their traditional pedagogical approach had no choice but to switch entirely to online teaching-learning. The article covers the importance of online learning and analysis of the Strengths, Weaknesses, Opportunities, & Challenges of e-learning mode in times of crisis. This article also highlights the growth of online learning during times of pandemics and natural disasters and includes advice for educational institutions on how to deal with the challenges associated with online learning.